Silliman Journal - Cubelo, Jose Edwin (Silliman Journal, 2023)
The study analyzed the status and constraints of smallhold coconut farmers in Negros Oriental, Philippines to provide the basis for interventions geared to-wards boosting their productivity and income. Primary data were obtained from key informants at the Philippine Coconut Authority (PCA), and from coconut farm-ers in nine municipalities in the province using survey methodology. Secondary data were also collected. The participating farmers are small scale with coconut landholdings averaging 1.40 hectares, slightly larger than the provincial average of 1.32 ha, but about a hectare smaller than the national average of 2.4 ha. Almost all are members of small coconut farmers' organizations (SCFOs). Among the PCA-initiated programs, majority (56.4%) have availed of the corn seed dispersal project for intercropping, 39.8% participated in trainings on coconut-related technologies, and not many (19.5%) have availed of the "plant-now-pay-later" program (PNPL) involving improved coconut varieties. Majority have experienced a decline in coco-nut yield that was mainly attributed to poor crop nutrition, the most neglected agronomic practice. Many follow a corn-coconut intercropping scheme in about one-third of their coconut land holdings. Practically no product diversification and very little value-adding activities are taking place with almost everyone Opting to produce and sell only copra from their coconut trees. Based on the existing realities of the responding farmers, the following prob-lems and constraints were ascertained: 1) low coconut yield due to poor agro-nomic practices; 2) low farm productivity due to underutilization of land resources; 3) low farm income due to, among others, the absence of product diversification and value-adding activities; 4) inefficient marketing system; and 5) lack of access to support services, particularly in the area of production credit. A set of interven-tions is suggested to address the plight of this farming sector.